KEARIFAN LOKAL MASYARAKAT DAYAK MERATUS DALAM PENGELOLAAN HUTAN SECARA TRADISIONAL DI DESA ATIRAN - Miftahul Anwar; Hafizianor Hafizianor; Asysyifa Asysyifa (Jurnal Sylva Scienteae, 2023)
The people of Atiran Village as the Dayak Meratus tribe are very dependent on the forest, their average livelihood is as farmers who use the forest for farming, gardening and hunting. The importance of forests for the socio-economic life of a society is now felt to be increasing because cultural values in the form of human wisdom in managing nature are believed to be the best way to manage nature. This study aims to examine the material infrastructure aspect of the local wisdom of the Meratus Dayak community in Atiran Village. Data collection was done by field observations and interviews. Respondents were determined by purposive sampling method. Data processing is carried out by inductive qualitative analysis, which provides a general and comprehensive picture of the actual situation. Based on the results of research on local wisdom of the Meratus Dayak community in traditional forest management in Atiran Village, namely the cultivation pattern carried out by the Atiran Village community with a "gilir balik" cultivation pattern followed by rituals and customary rules and the Meratus Dayak community always uses land that is no longer productive again to be used as a forest gardenMasyarakat Desa Atiran sebagai suku Dayak Meratus sangat bergantung besar kepada hutan, rata-rata mata pencaharian mereka adalah sebagai petani yang memanfaatkan hutan untuk berladang, berkebun dan berburu. Pentingnya hutan bagi kehidupan sosial ekonomi suatu masyarakat kini dirasakan semakin meningkat karena nilai budaya berupa kearifan manusia dalam mengelola alam itulah yang diyakini merupakan cara yang paling baik dalam mengelola alam. Penelitian ini bertujuan untuk mengkaji aspek infrastruktur material pada kearifan lokal masyarakat Dayak Meratus di Desa Atiran. Pengambilan data dilakukan dengan observasi lapangan dan wawancara. Responden ditentukan dengan metode purposive sampling. Pengolahan data dilakukan dengan analisis kualitatif secara induktif yaitu memberikan gambaran secara umum dan menyeluruh tentang keadaan yang sebenarnya. Berdasarkan hasil Penelitian kearifan lokal masyarakat dayak meratus dalam pengelolaan hutan secara tradisional di Desa Atiran yaitu pola perladangan yang dilakukan oleh masyarakat Desa Atiran dengan pola perladangan “gilir balik” yang diikuti dengan ritual dan aturan adat serta masyarakat Dayak Meratus selalu memanfaatkan lahan yang sudah tidak produktif lagi untuk dijadikan kebun hutan (forest garden).